Bakers Cyst and its Analog on Elbow - Stojanović, Milovan; Stojanović, Sonja; Nedović, Jovan; Božilov, Slađana (Indian Journal of Pharmacy Practice)
Bakers cyst is synovial cyst that is located in popliteal fossa. Rupture of meniscus and inflammatory diseases of synovial joints are the most common cause of Bakers cyst. Cyst diagnosis is based on a clinical picture, the ultrasound of knee and popliteal fossa and/or magnetic resonance imaging of the knee. The treatment includes bed rest, physical procedures, drugs, puncture and/or surgical removal of the cysts. All the above methods are effective in the treatment of cyst but not in the treatment of diseases that have led to the development of synovial effusion and the formation of cysts. Therefore, it is necessary to emphasize the importance of treating the primary disease that caused synovial cyst. Synovial cyst of knee joint is relatively common finding while cyst on elbow is a rare phenomenon.
Keywords: Bakers cyst; Synovial cyst; Corticosteroids; Methotrexate; Elbow.